Health professional as educator : principles of teaching and learning - Susan Bacorn Bastable; Deborah Sopczyk; Pamela Gramet; Karen Jacobs; Margaret M. Braungart (Burlington, Massachusetts : Jones & Bartlett Learning, 2020)
"Health Professional as Educator: Principles of Teaching and Learning focuses on the role of health professionals as an educator of patients, clients, staff, and students in both clinical and classroom settings. This text covers teaching and learning techniques as well as strategies, learning styles, and teaching plans"--Provided by publisher
Keywords: Apprentissage; Education, Professional